Benang Merah Radikalisme Islam Kontemporer dengan Doktrin Keagamaan Khawarij - Muhammad Fahmi; Saefullah Azhari; Syaifuddin; Senata Adi Prasetia; Suwatah; Qudus Nofiandri Eko Dwi Sucipto; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2023)
This article delves into the contemporary phenomenon of Islamic radicalism with a specific emphasis on its connection to the religious doctrine of the Khawarij. The Khawarij, as a group that emerged in the early history of Islam, holds significant influence in comprehending the roots of radicalism in the modern Islamic world. The research aims to analyze and identify the common thread linking the religious doctrine of the Khawarij to the development of contemporary Islamic radicalism. Through a textual and historical analysis approach, the author explores key Khawarij concepts that remain relevant in shaping the mindset and actions of modern radical groups. Furthermore, the article highlights efforts for the prevention and mitigation of Islamic radicalization by detailing strategies that can be adopted by society, government, and religious institutions. Thus, it is anticipated that this article will contribute to a deeper understanding of the dynamics of contemporary Islamic radicalism and provide valuable insights for mitigation efforts.